ChemInform Abstract: Synthesis and Characterization of N‐Substituted (S)‐1, 2, 3, 4‐Tetrahydroisoquinoline‐3‐carboxamides and Thioamides as Organocatalysts for Asymmetric Aldol Reaction. Issue 3 (January 2015) - Drabina, Pavel; Androvic, Ladislav; Panov, Illia; Harmand, Lydie; Padelkova, Zdenka; Sedlak, Milos
Abstract Title compounds (I) are synthesized and tested as catalysts for aldol reaction of nitrobenzaldehyde (II) with acetone.